Apraglutide, a novel glucagon‐like peptide‐2 analog, improves fluid absorption in patients with short bowel syndrome intestinal failure: Findings from a placebo‐controlled, randomized phase 2 trial. Issue 4 (7th September 2021) - Eliasson, Johanna; Hvistendahl, Mark K.; Freund, Nanna; Bolognani, Federico; Meyer, Christian; Jeppesen, Palle B.
Abstract: Background: Treatment with glucagon‐like peptide‐2 (GLP‐2) analogs improve intestinal adaptation in patients with short bowel syndrome–associated intestinal failure (SBS‐IF) and may reduce parenteral support requirements. Apraglutide is a novel, long‐acting GLP‐2 analog designed for once‐weekly dosing. This trial investigated the safety and efficacy of apraglutide in patients with SBS‐IF. Methods: In this placebo‐controlled, double‐blind, randomized, crossover phase 2 trial, eight adults with SBS‐IF were treated with once‐weekly 5‐mg apraglutide doses and placebo for 4 weeks, followed by once‐weekly 10‐mg apraglutide doses for 4 weeks, with a washout period of 6–10 weeks between treatments. Safety was the primary end point. Secondary end points included changes from baseline in urine volume output compared with placebo, collected for 48 h before and after each treatment period. Results: Common treatment‐related adverse events (AEs) were mild to moderate and included polyuria, decreased stoma output, stoma complications, decreased thirst, and edema. No serious AEs were considered to be related to apraglutide treatment. The safety profile was comparable for the lower and higher doses. Treatment with once‐weekly 5‐ and 10‐mg apraglutide doses significantly increased urine volume output by an adjusted mean of 714 ml/day (95% CI, 490–939; P < .05) and 795 ml/day (95% CI, 195–1394; P < .05), respectively, compared with placebo, with no significant differences between doses. Conclusions: Once‐weekly apraglutide was well tolerated at both tested doses and significantly increased urine volume output, providing evidence for increased intestinal fluid absorption. A phase 3 trial is underway in adults with SBS‐IF.